2023
DOI: 10.1371/journal.pone.0290834
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported benefits and risks of open water swimming to health, wellbeing and the environment: Cross-sectional evidence from a survey of Scottish swimmers

David M. Oliver,
Craig W. McDougall,
Tony Robertson
et al.

Abstract: Engaging with natural environments benefits human health by providing opportunities for social interactions, enhancing mental wellbeing and enabling outdoor spaces for physical exercise. Open water swimming has seen a rapid increase in popularity, partly due to the physical health benefits it can provide but also with the growing interest in (re)connecting with nature for environment-health interactions. Using a national-scale online survey of 717 open water swimmers, the aim of this study was to investigate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
1
0
0
Order By: Relevance
“…More physical exercise was associated with better self-reported health, fewer somatic symptoms, and greater well-being for both women and men. These findings are consistent with previous studies that have found physical exercise to be relevant to an individual's health and well-being (Biddle et al 2018;Forte et al 2023;Kvam et al 2016;Oliver et al 2023).…”
Section: Discussionsupporting
confidence: 92%
“…More physical exercise was associated with better self-reported health, fewer somatic symptoms, and greater well-being for both women and men. These findings are consistent with previous studies that have found physical exercise to be relevant to an individual's health and well-being (Biddle et al 2018;Forte et al 2023;Kvam et al 2016;Oliver et al 2023).…”
Section: Discussionsupporting
confidence: 92%